Effects of interoceptive accuracy on timing control in the synchronization tapping task - Tomyta, Kenta; Katahira, Kentaro; Ohira, Hideki (Frontiers in Neuroscience, 2023)
Humans often perform rhythmic synchronized movements. Professional musicians and dancers particularly perform such movement tasks well and have a higher interoceptive accuracy (IAcc) than non-musicians and non-dancers. We thus hypothesized that rhythmic synchronized movements might be enhanced by a higher IAcc. To investigate this hypothesis, this study conducted a heartbeat counting task and a rhythmic synchronization tapping task with normal (easier) and slow (harder) tempi metronomes. Inconsistent with our hypothesis, however, a higher IAcc was negatively correlated with timing control, but only in the slow tempo condition [r (30) = 0.46, p < 0.05]. This suggests that a higher IAcc did not enhance timing control in rhythmic synchronized movements but rather weakened it, resting heart rate variability was not correlated with timing control.